The Response of the Northern Hemisphere Storm Tracks and Jet Streams to Climate Change in the CMIP3, CMIP5, and CMIP6 Climate Models. Issue 23 (11th December 2020) - Harvey, B. J.; Cook, P.; Shaffrey, L. C.; Schiemann, R.
Abstract: The representation of the Northern Hemisphere (NH) storm tracks and jet streams and their response to climate change have been evaluated in climate model simulations from Phases 3, 5, and 6 of the Coupled Model Intercomparison Project (CMIP3, CMIP5, and CMIP6, respectively). The spatial patterns of the multimodel biases in CMIP3, CMIP5, and CMIP6 are similar; however, the magnitudes of the biases in the CMIP6 models are substantially lower. For instance, the multimodel mean RMSE of the North Atlantic storm track for the CMIP6 models (as measured by time‐filtered sea‐level pressure variance) is over 50% smaller than that of the CMIP3 models in both winter and summer, and over 40% smaller for the North Pacific. The magnitude of the jet stream biases is also reduced in CMIP6, but by a lesser extent. Despite this improved representation of the current climate, the spatial patterns of the climate change response of the NH storm tracks and jet streams remain similar in the CMIP3, CMIP5, and CMIP6 models. The SSP2‐4.5 scenario responses in the CMIP6 models are substantially larger than in the RCP4.5 CMIP5 models, which is consistent with the larger climate sensitivities of the CMIP6 models compared to CMIP5. Plain Language Summary: The ability of the climate models used in the CMIP (Coupled Model Intercomparison Project) models to represent the Northern Hemisphere storm tracks and jet streams is evaluated. The newest models (CMIP6) are found to have a much better representation, especially for the North Atlantic. The response of the storm tracks and jet streams to climate change is also assessed. The spatial pattern of the response in the CMIP3, CMIP5, and CMIP6 models is found to be similar. The response of the new CMIP6 models to the SSP2‐4.5 scenario is found to be larger than that of the very similar RCP4.5 scenario in the CMIP5 models, suggesting the CMIP6 models are more sensitive to the forcing from climate change. Key Points: The spatial patterns of the historical CMIP3, CMIP5, and CMIP6 biases are similar, but their magnitudes are substantially smaller in CMIP6 The spatial patterns of the climate change responses in the NH storm tracks and jet streams are similar in the CMIP3, CMIP5, and CMIP6 models The SSP2‐4.5 response in CMIP6 is larger than the RCP4.5 CMIP5 response, consistent with the larger climate sensitivities in CMIP6